A new relation between preferred inclinations and mean radial velocity of the cluster - Aryal, B; Yadav, D (Scientific World, 2011)
We worked on POSSII and ESO films and measured the diameters and position angles of 5,688 galaxies in 34 clusters using 25-fold magnification microscope. The inclinations of individual galaxies are determined using Holmberg’s method and their distributions are studied. The expected distributions are compared with the fitted curves. For this, we used linear, polynomial (second order) and Gaussian fits. We noticed a relation between the preferred inclination angle of the cluster and their mean radial velocity. Possible explanations of the result will be discussed. Keywords: Galaxies; Evolution - galaxies; Formation - galaxies; Statistics - galaxies; Clusters DOI: http://dx.doi.org/10.3126/sw.v9i9.5512 SW 2011; 9(9): 18-24